2023
DOI: 10.1002/anie.202218507
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Propagation of a Minimal Catalytic RNA Network in GUV Protocells by Temperature Cycling and Phase Separation

Abstract: Compartmentalization is key to many cellular processes and a critical bottleneck of any minimal life approach. In cells, a complex chemistry is responsible for bringing together or separating biomolecules at the right place at the right time. Lipids, nucleic acids and proteins self-organize, thereby creating boundaries, interfaces and specialized microenvironments. Exploiting reversible RNA-based liquid-liquid phase separation (LLPS) inside giant unilamellar vesicles (GUVs), we present an efficient system capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…This can be achieved by adding equimolar concentrations of sucrose and glucose in the inner and outer solution, respectively. While concentrations up to 900 × 10 −3 m of sucrose/glucose have been used, [ 142 ] the effect of these high concentrations of sugar on protein and membrane properties have barely been studied. [ 171 ] As an alternative to using sugars, density gradient medium OptiPrep has been successfully used in cDICE and eDICE.…”
Section: Strengths and Limitations Of Current Methods: A Comparative ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This can be achieved by adding equimolar concentrations of sucrose and glucose in the inner and outer solution, respectively. While concentrations up to 900 × 10 −3 m of sucrose/glucose have been used, [ 142 ] the effect of these high concentrations of sugar on protein and membrane properties have barely been studied. [ 171 ] As an alternative to using sugars, density gradient medium OptiPrep has been successfully used in cDICE and eDICE.…”
Section: Strengths and Limitations Of Current Methods: A Comparative ...mentioning
confidence: 99%
“…Inverted emulsion has been used for, among other systems, reconstitution of actin cortices, [90] encapsulation of tubulin, [143] in vitro transcription-translation (IVTT) systems [119,144,146,150,[152][153][154] RNA organelles, [142] and FtsZ filaments, [147,148] up to full in vitro reconstitution of the E. coli divisome machinery (including MinCDE, FtsZ, and FtsA). [149] Likewise, cDICE has been used to encapsulate a wide variety of systems.…”
Section: Encapsulation Of Complex Solute Mixtures In Physiological Bu...mentioning
confidence: 99%
“…As samples were located above the aperture center of the Peltier T-plate, a heat gradient between sample and T-plate was forming leading to a deviating sample temperature (Figure S6a-c). To be able to convert the set temperature into the actual sample temperature, a calibration was performed as previously described [28] , using an infrared camera (Xi80, Optris, Berlin, Germany). Briefly, the temperature of the glass slide surface (on which the vesicles sediment) was measured in steps of 5 °C over the entire FT-temperature regime.…”
Section: Methodsmentioning
confidence: 99%
“…Our group previously demonstrated that FT cycling induces the exchange of vesicular contents between distinct populations of lipid GUVs in the absence of vesicle fusion [26] . Moreover, we have shown in other studies that such cyclic temperature changes can be exploited to propagate catalytically active RNAs within a population of GUVs and that the presence of temperature‐sensitive RNA organelles can even improve the propagation of such minimal catalytic RNA networks by implementing spatiotemporal control in GUVs [27,28] . Relating to the phase transition of membrane lipids, we hypothesized that transient periods of membrane destabilization result in an increased permeability allowing for a diffusion‐based mixing of contents across vesicle membranes.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation